How can academic engagement and flow of medical students be promoted? The roles of perceived autonomy and teacher support - Majid Sadoughi; Najmeh Eskandari (Journal of Medical Education Development)
Background & Objective: One of the most considerable concerns of higher education systems is how to enhance students’ academic engagement and flow. The present study aimed to examine the roles of emotional and autonomy support provided by teachers in students’ academic engagement and flow. Material & Methods: The study sample included students enrolled at Kashan University of Medical Sciences in winter 2023. A total of 356 students were chosen as participants using proportional stratified random sampling technique. The data collection instruments were Black and Deci’s Perceived Autonomy Support Questionnaire, Sakiz’s Teacher Emotional Support Questionnaire, Reeve and Tseng’s Academic Engagement Questionnaire, and Martin and Jackson’s Academic Flow Questionnaire. The data were analyzed using Structural Equation Modeling (SEM) in Amos-22 software. Results: The SEM results indicated that the proposed model had a good fit. Perceived autonomy support predicted academic engagement (ß =.692, p <0.01) and academic flow (ß = 0.335, p < 0.01), and perceived emotional support predicted academic engagement (ß = 0.226, p < 0.01) and academic flow (ß = 0.312, p < 0.01). Conclusion: The results highlight the importance of the roles of perceived autonomy and emotional support in students’ academic engagement and flow. Therefore, medical science universities are recommended to improve the quality of students’ learning to achieve higher levels of academic success by giving professors essential guidelines on how to provide students with more autonomy and emotional support.